ANALISIS DEBIT BANJIR RENCANA PADA SEI PUTIH (STUDI KASUS) - TOLHAS TRI JAWANTORO LUMBAN GAOL; RIZKY FRANCHITIKA (JURNAL ILMIAH SIMANTEK, 2023)
Sei Putih is one of the rivers whose flow crosses the settlements of Medan City residents. Flood-prone areas in theplanning area include river estuaries, floodplains especially along Sei Putih. To protect against floods in rivers, a plan forsafeguarding against flooding can be carried out by planning buildings that aim to reduce the damage caused byflooding to the minimum level. The control planning can be carried out well if the rainfall data at each rain station can beknown and the discharge calculated using a Synthetic Unit Hydrograph. The hydrograph method used is the NakayasuSynthetic Unit Hydrograph. This method aims to analyze the amount of planned rainfall that may occur in Sei Putih until2070 and analyze the design flood discharge to evaluate the magnitude of the design flood discharge at various returnperiods of 2, 5, 10, 25, 50 years. In the results of the rainfall analysis used to calculate rainfall intensity is the value of thePearson Log III rainfall distribution for the 10-year return period (2012-2021). From the calculation results, it is obtainedthat the maximum rainfall that will occur is 620.35 mm, and the planned flood discharge for the HSS Nakayasu returnperiod of 2,5,10,25,50 years is 130.58 m³/d, 150,488 m³/d, 160 .48 m³/d, 168.799 m³/d, 184.56 m³/d and 171.295 m³/d.The results of the study show that the flood discharge from year to year has increased, therefore it is necessary tomaintain or scrape the river.